Eosinophilic esophagitis (EoE); a disease that must not be neglected - implications of esophageal rupture and its management - Larsson, Helen (BMC Gastroenterol, 2020)
BACKGROUND: The prevalence of Eosinophilic esophagitis (EoE) is increasing, a severe complication of EoE is spontaneous perforation of the oesophagus. It is of great importance to be aware of this risk and handle this severe complication carefully. CASE PRESENTATION: A middle-age man with EoE since 2004, had a total esophageal bolus obstruction while eating lunch at the local hospital. Drinking water, in an attempt to release it, led to a total intramural ruptur of the esophageal wall. A CT scan detected the injury and a covered esophageal stent was inserted within 2 h from the injury. Despite the immediate hospital care, he developed mediastinitis, were in need of a laparascopy and intensive care. After 8 weeks the stent was removed and the esophagus was considered healed. Biopsies from the esophagus showed an eosinophilic inflammation (65 eosinophils/HPF). Twelve weeks from the injury he was essentially back in his normal state and was discharged from the hospital. He was placed on a 6 weeks course of topical treatment with budesonide, which needed to be extended due to inadequate remission. Remission was achieved after 12 weeks of treatment. CONCLUSION: An effective topical steroid treatment in EoE patients is important. EoE patients are in risk of oesophageal perforation, if so, management may be conservative but mediastinal drainage is important if significant extravasation occurs and should be instituted from the start.